2014
DOI: 10.5152/iao.2014.017
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nonylphenol on Hearing in Rats

Abstract: OBJECTIVE:Nonylphenol is a neurotoxic substance widely present in the environment. Although its neurotoxic effects are well-known, to our knowledge, the ototoxic effects of nonylphenol on hearing have not been published in the literature yet. We aimed to investigate the effect of nonylphenol on hearing function in rats. MATERIALS and METHODS:Fifty rats were randomly divided into five Groups each containing 10 animals. Group 1 was a control Group and Group 2 was a solvent control containing ethanol alone, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Laboratory studies on animals have demonstrated adverse effects of NP, such as on reproduction, development, neurotoxicity and inflammation ( Jie et al, 2013 ; Yücedağ et al., 2015 ). The responsibility of organisms are various by the exposing dose and duration, and the exposing time of life cycle ( Patisaul & Adewale, 2009 ; Solecki et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies on animals have demonstrated adverse effects of NP, such as on reproduction, development, neurotoxicity and inflammation ( Jie et al, 2013 ; Yücedağ et al., 2015 ). The responsibility of organisms are various by the exposing dose and duration, and the exposing time of life cycle ( Patisaul & Adewale, 2009 ; Solecki et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…NF'nin erkek üremesini etkilediği ve pankreas da dahil olmak üzere çeşitli organlara zararlı olduğunu gösteren kanıtlar da mevcuttur [12]. Yücedağ ve ark.,'nın [13] yaptığı diğer bir çalışmada sıçanlarda NF'nin işitme fonksiyonu üzerinde olumsuz etkilere sahip olduğu gösterilmiştir. Ergün ve ark., [14]'nın yaptığı diğer bir 73 çalışmada; NF ve BFA'nın çevresel dozlarının (0,001; 0,1; 1, 10 ve 100 µg NF/ml ve 0,001; 0,1; 1, 10 ve 100 µg BFA/ ml) sığırlarda sperm DNA'sına ve oosit olgunlaşmasına etkileri belirlenmiştir.…”
Section: Nonilfenol 'üN Genel öZellikleriunclassified
“…
Dear Editor, I read with great interest the recent study by Yücedağ et al [1] entitled "The Effects of Nonylphenol on Hearing in Rats." It needs to be specified in the article if the hearing levels of the rats were evaluated before the study or not.

Another point I would like to emphasize is that the hearing levels of the rats after the application of ethanol and nonylphenol were evaluated by distortion product otoacoustic emission (DPOAE).

…”
mentioning
confidence: 99%
“…Dear Editor, I read with great interest the recent study by Yücedağ et al [1] entitled "The Effects of Nonylphenol on Hearing in Rats." It needs to be specified in the article if the hearing levels of the rats were evaluated before the study or not.…”
mentioning
confidence: 99%